Immune Characteristics in Biliary Atresia Based on Immune Genes and Immune Cell Infiltration - Yang, Chenyu; Xing, Huiwu; Tan, Bingqian; Zhang, Mingman (Frontiers in Pediatrics, 2022)
Background: Biliary atresia (BA) is a serious biliary disease in infancy. Jaundice is the main clinical manifestation, mainly bile duct cell injury and loss of intrahepatic and extrahepatic bile duct. If left untreated, it will eventually lead to liver cirrhosis. The pathogenesis of BA is not clear, and now it is widely believed that BA is an autoimmune disease. However, few studies have revealed the infiltration of immune cells in the liver of BA from a global perspective. We used liver tissue sequencing data to predict the infiltration and relative content of immune cells in BA. Methods: The BA datasets GSE46960, GSE15235, GSE84044 and patients’ information were downloaded from the Gene Expression Omnibus (GEO) database. After batch normalization, the differentially expressed immune genes (DE-IGs) in BA liver, normal liver and hepatitis B liver were analyzed with the cut-off value of |log2fold change|(log2FC) > 1 and false discovery rate (FDR) <0.05. IBERSORT software was used to predict the proportions of 22 immune cells in all samples of the datasets. Results: 73 DE-IGs have been screened out between BA and normal tissue, among them, 20 genes expressed highly and another 53 expressed low. 30 DE-IGs existed between inflammation and fibrosis livers of BA and all of them were low expression in fibrosis livers of BA. In GO terms analysis, these DE-IGs mainly associated with MHC protein complex, cytokine, chemokine activity, MHC-Ⅱ receptor activity. In KEEG pathway analysis, the DE-IGs mainly enriched in pathways of Th1 and Th2 cell differentiation, Th17 cell differentiation, IL-17 signaling pathway, Toll−like receptor signaling pathway, TNF signaling pathway, and autoimmune diseases. There were significant differences in immune infiltration among different pathological types of BA, and there were also obvious differences in immune infiltration of hepatitis B as a disease control of BA. Conclusion: Based on immune genes and immune cell infiltration, this paper reveals the immune characteristics of biliary atresia from a global point of view, which provides a new perspective for understanding the pathogenesis of BA and provides a direction for the diagnosis and treatment of BA.